Differential item functioning analysis using the SF-36 in patients with lumbar disc herniation: A quality of life research (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Differential item functioning (DIF) presents when individuals from different groups perceive the meaning of items differently in health-related quality of life (HRQoL) questionnaires. The aim of this study is to distinguish DIF in the SF-36 questionnaire and to determine its effect on comparison of HRQoL scores of lumbar disc herniation (LHD) patients and a healthy population.Methods: A total of 137 patients with LHD and 691 healthy individuals filled out the Persian version of the SF-36 questionnaire. The Rasch model was used to assess DIF for patients with LDH and a healthy population.Results:  The presence of DIF was determined in 6 of 8 (75%) domain scores between patients with LDH and healthy individuals. Although half of the DIF was categorized as either negligible (3 out of 8; 37.5%), high DIF was observed in 3 out of 8 domains (37.5%). Gender was not flagged as important to DIF, with only 3 of 8 (37.5%) categorized as negligible.Conclusion: Because the use of the SF-36 questionnaire in HRQoL assessment between groups may not be invariant, caution should be used during comparison of HRQoL scores between heterogeneous groups.